Management of Pilon Fractures—Current Concepts - Mair, Olivia; Pflüger, Patrick; Hoffeld, Kai; Braun, Karl F.; Kirchhoff, Chlodwig; Biberthaler, Peter; Crönlein, Moritz (Frontiers in Surgery, 2021)
Tibial pilon fractures were first described by Étienne Destot in 1911. He used the French word „pilon“ (i.e. pestle), to describe the mechanical function of the distal tibia in the ankle joint. This term has further been used to portray the mechanism involved in tibial pilon fractures in which the distal tibia acts as a pestle with heavy axial forces over the talus basically causing the tibia to burst. Many different classification systems exist so far, with the AO Classification being the most commonly used classification in the clinical setting. Especially Type C fractures are extremely difficult to manage as the high energy involved in developing this type of injury frequently damages the soft tissue surrounding the fracture zone severely. Therefore long -term outcome is often poor and correct initial management crucial. In the early years of this century treatment has evolved to a two – staged protocol, which nowadays is the gold standard of care. Additional methods of treating the soft tissue envelope are currently being investigated and have shown promising results for the future. The aim of this review is therefore to summarize protocols in managing these difficult fractures, review the literature on recent developments and therefore give surgeons a better understanding and ability to handle tibial pilon fractures.